Produksi dan Evaluasi Antibodi Poliklonal untuk Deteksi Toksin Photorhabdus spp. - Yadi S Suryadi; Ifa S Manzila; Alina Thenawidjaya Akhdiya; Etty Pratiwi (Jurnal AgroBiogen, 2006)
Production and Evaluation of Polyclonal Antibody forDetection of Photorhabdus spp. Toxin. Yadi Suryadi, IfaManzila, Alina Akhdiya, and Etty Pratiwi. The researchwas aimed to produce and evaluate polyclonal antibody(PAb) for specific Photorhabdus spp. bacterial toxin detection.Photorhabdus spp. toxin of HJ isolates which was purifiedusing Hi Prep. 16/60 Sephacryl S-200 HR column chromatographyrevealed three different peaks of polypeptides.The results showed that the protein concentration of crudeantigen protein (supernatant) was 3,711 μg/μl, whilst fractionof protein was 1,95 x 10-2 μg/μl, respectively. The bioassayusing Tenebrio molitor larvae-3 indicated that after 48 happlication, the percentage of larvae mortality by crude antigenwas lower (73%) than by fraction antigen (93%). Basedupon NCM-ELISA test, PAb of fraction protein derived fromHJ isolate reacted with Photorhabdus spp. antigen yieldedstronger or darker violet color on membrane than that ofcrude protein. In addition, it was observed that PAb coulddifferentiate specifically Photorhabdus spp. toxin with otherbacterial filtrate such as Xanthomonas oryzae pv oryzae, X.campestris pv glycinea, Ralstonia solanacearum, Pseudomonassyringae pv glycinea and P. fluorescens, however itshowed cross reaction with Escherichia coli. Further testsare needed in optimizing PAb-Photorhabdus spp. sensitivityto achieve effective concentration for detection of Photorhabdusspp. toxin as well as specificity test against otherbacterial antigens.